PENGARUH PENGAJARAN SPIRITUALITAS PERSAUDARAAN KASIH DAN DAMAI TERHADAP PEMBENTUKAN KARAKTER ANAK DI PANTI ASUHAN ST. ALOISIUS MADIUN - Lote, Alfa Edison; Wilhelmus, Ola Rongan (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2021)
The spirituality of the Brotherhood, Love and Peace aims to produce a comfortable, pleasant, joyful and peaceful life of a community. The main problem of the study is the lack of influence of knowledge and application of spirituality of the Brotherhood, Love and Peace related to the character building of the orphanage boy. The purpose of the study was to analyze relationship between spirituality teaching of the Brotherhood, Love and Peace and the character building of the orphanage boys. The research method used in the study is quantitative. Based on the results of this study, it can be concluded that the majority (46.7%) of respondents understand and appreciate well what is spirituality in general. The results of the study also showed that the majority (66.7%) of respondents understand well the spirituality of brotherhood of love and peace. In addition, the majority (70%) of respondents understand what characters and character education. Finally, the results of data analysis also show that the majority of respondents said there was a positive influence of the Spirituality of the Brotherhood of Love and Peace on the character building of students at the Saint Aloisius orphanage Madiun.